Problematika Melanggar Aturan Sekolah (Studi Kasus Siswa yang Melanggar Aturan Dalam Proses Pembelajaran di SMKN 1 Bukittinggi) - Lastri Lastri; Elviana Elviana; Nelmita Nelmita (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
This article explores a case study of students violating rules at SMKN 1 Bukittinggi, focusing on the types of violations, triggering factors, the impact on academic achievement, and the school's efforts to address the issue. Utilizing a qualitative approach, including interviews, observations, and content analysis, this research delves into the complex internal dynamics of the school and external factors influencing student behavior. The research results highlight various rule violations, starting from non-compliance with class rules such as violations of the rules in the PBM. Triggering factors encompass personal aspects, family environment, and social pressures. The school has implemented various mentoring programs. Nevertheless, continuous evaluation is necessary to adjust the effectiveness of these programs. The role of parents is also acknowledged as crucial in supporting the school's efforts.. By recommending measures such as community involvement, policy reinforcement, and the use of technology for monitoring, this article presents a comprehensive perspective to assist schools in addressing similar challenges. It is anticipated that these findings contribute positively to further discussions on enhancing discipline and the learning environment in vocational high schools.